Pro iOS continuous integration - Pouclet, Romain (Apress, 2014)
Pro iOS Continuous Integration teaches you how to utilize the strengths of continuous integration in your everyday work. CI is more popular now than ever, as iOS developers realize how time-consuming building and deploying an application for testing purposes and quality assurance can be. This book shows you how to make your developing life easier, with real-world applications and examples. With this book, you will learn what continuous integration and continuous delivery really are and how they can be used in your iOS projects. You will learn how to release an iOS application outside the App Store using Xcode. You'll understand how to leverage the power of the command line to build your projects, and run your tests. You'll use Jenkins and Bamboo to architect automatic builds and automate the whole build process. In addition, you'll also learn how to use Xcode server and bots, what quality assurance tools can be used to measure the quality of your code, and how to send builds to your beta testers. Author Romain Pouclet provides hands-on, practical experience in iOS continuous integration and, using this book, you will see that it's not actually that hard to set up a fully-featured continuous integration platform, whether you are an independent iOS developer working from home or a member of a team in a big company.